Political Ideas and the Problem of the Regime in Peru, 1830-1930 - Hernando Nieto, Eduardo (2004)
This article analyses Peruvian political thought during the nineteenth and twentieth centuries from a Straussian perspective. The author points out that this "Straussian reading of our political history" encompasses what Strauss understood as the first and second waves of modernity. Thus, during the 19th century, Peru defined its state and political regime under the influence of the ideas of the first wave of modernity. During this period, liberal and conservative discourse emerged, with more similarities than differences. Among the conservatives, Bartolomé Herrera was prominent, using rational arguments to proclaim an authoritarian regime. In the liberal camp, Benito Lazo and Francisco de Paula Gonzáles were advocates of scientific progress, solidarity and charity. In the second wave, on the other hand, Peru faced problems of identity and social exclusion. The presence of intellectuals such as Manuel Gonzales Prada, José Carlos Mariátegui and Víctor Raúl Haya de la Torre contributed to the development of various ideological currents, such as positivism and nationalism, which influenced the evolution of Peruvian political thought and the construction of a national identity.